The Cultural Lives of Greyhounds - Stokes, John. author. aut Link
XIX, 348 p. 39 illus. in color.
Keywords: This book aims to enhance our intellectual understanding of the relationship between human beings and domestic animals, with a focus on a specific breed of dog: the greyhound. It combines literary criticism, cultural history and the rapidly expanding field of human/animal studies by tracing the creative representation of the greyhound, from the earliest references in classical myth to multiple appearances in contemporary literature, performance and the fine arts. Each representation—whether of hunter or racer, of pet or predator—is treated not simply as a stage in some inevitable humanitarian progression but as part of a series of co-evolutionary exchanges between humans and their canine collaborators that together constitute a shared experience. Writers who have been fascinated by greyhounds range from Shakespeare to Dryden, from William Wordsworth to George Meredith, from Marcel Proust to Colette, from William Butler Yeats to Ted Hughes and beyond. The haunting image of the breed has inspired artists such as Dürer, Hogarth and Giacometti. John Stokes is Emeritus Professor of Modern British Literature in the Department of English at King's College London, UK. His publications include In the Nineties (1990), Oscar Wilde: Myths, Miracles and Imitations (1996) and The French Actress and her English Audience (2005), as well as numerous academic articles and reviews. He co-edited The Cambridge Companion to the Actress (2007) and two volumes of journalism for The Complete Works of Oscar Wilde (2013). He is a regular reviewer for the Times Literary Supplement.